Klippel-Trenaunay syndrome with small vessel pulmonary arterial hypertension. Issue 11 (1st November 2005) - Ulrich, S; Fischler, M; Walder, B; Pfammatter, T; Speich, R
Abstract : A patient with Klippel-Trenaunay syndrome and pulmonary arterial hypertension not associated with chronic thrombo-embolic pulmonary hypertension is described. It is hypothesised that pulmonary arterial hypertension is another complication associated with the Klippel-Trenaunay syndrome, possibly due to haemodynamic changes of small vessel abnormalities.